Comparison between the results of proximal femur nail anti-rotation and cemented bipolar hemiarthroplasty in treatment of intertrochanteric fractures in Sanglah Hospital in 2016 - Dusak, Wayan Suryanto; Simanjuntak, Herryanto Agustriadi; Putra, I Gusti Ngurah Paramartha Wijaya (International Journal of Research in Medical Sciences, 2019)
Background: Hemiarthroplasty is now being considered as a primary treatment for comminuted unstable type of IT fracture in elderly on the grounds that it allows early mobilization and full weight bearing. Recently popular modality is fourth generation of intramedullary nails like the Proximal Femoral Nails. The goal of treatment is restoring mobility safely and efficiently, while minimizing the risk of medical complications and technical failure. Methods: A Forty patients, having Intertrochanteric fractures treated with PFNA or cemented BH at our institution between April 2016 and April 2017. The primary outcomes measures were postoperative complication and hip function. The secondary outcome measures were intraoperative blood loss, transfusion rate, surgical time, postoperative haemoglobin and hospital stay. Results: Seventeen patients in PFNA group and 23 patients in BH group were included for analysis. There were no significant differences between the two group regarding to the Harris Hip Score at 6 months follow up. Significant differences were found between PFNA and BH group in comparison of intraoperative blood loss (p < 0.001), length of stay (p = 0.006), surgical time (p < 0.001), postoperative transfusion (p < 0.001), and decrease of hemoglobin (p=0.001). Conclusions: These findings indicate that PFNA has obvious advantages over the BH in treatment of intertrochanteric fractures in case of surgical trauma and postoperative complication.